Psychiatric disorders in psychosocially burdened mothers with young children: a population-based cohort study in Germany - Fricke, Julia; Bolster, Marie; Icke, Katja; Lisewski, Natalja; Kuchinke, Lars; Ludwig-Körner, Christiane; Schlensog-Schuster, Franziska; Reinhold, Thomas; Berghöfer, Anne; Roll, Stephanie; Keil, Thomas (Frontiers in Psychiatry, 2025)
IntroductionMothers are exposed to a variety of stressors in the early years of their children’s lives, being at risk for mental illness. The aim of our analysis was to estimate the type and frequency of and potential risk factors for psychiatric disorders in mothers with children aged up to three years.MethodsBased on random population samples from three urban areas in Germany, mothers of infants were recruited for a population-based cohort study as part of the SKKIPPI project. The subjects underwent a two-stage screening process at baseline: A standardized psychiatric diagnostic interview using the Mini International Neuropsychiatric Interview (M.I.N.I- 7) was conducted only with mothers who showed an elevated psychosocial and mental health burden. Mothers with specific psychiatric disorders were invited for follow-up after six months.Results814 mothers participated in the psychiatric interview, 304 in the follow-up. At baseline interview, 5% of the mothers had at least one current psychiatric disorder. Generalized anxiety disorders (2%) and major depressive episodes (1%) were the most common disorders. Of these mothers, 42% were still affected at the 6-month follow-up. Risk factors were having at least one strong stressor in life, a severe negative experience in the own childhood, a previously diagnosed psychiatric disorder, a low/medium educational level, and having already received support through early childhood support programs.DiscussionThe occurrence of psychiatric disorders in mothers with young children seemed lower than previously reported, in the majority symptoms disappeared after 6 months. The study provides important information on the frequency of psychiatric disorders in this group and enables care services to be adapted to meet their needs.